The Integrated software and informational system “KROS” - Gonchariuk, N.V.; Makarov S.F.; Mihailov A.L. (Problems of the Regional Energetics)
The article describes functions of the information system “KROS”, which consists 2 subsystems “BOS” (block of dispatcher’s schemes) and “BARS”. Complex “BARS” works for organizing a base of calculation circuits of power pools and regions, which have different level and volume. After equivalent or pooling circuit construction there are creates and uses new calculation circuits of two types (search network and equivalence network).